2020
DOI: 10.5888/pcd17.200012
|View full text |Cite
|
Sign up to set email alerts
|

Telepharmacy and Quality of Medication Use in Rural Areas, 2013–2019

Abstract: What is already known on this topic? Pharmacy closures disrupt medication access and decrease patient adherence to prescription medications. Telepharmacy is a potential solution to this problem; however, research on the relationship between telepharmacy and adherence, as well as other aspects of the quality of medication use, is limited. What is added by this report? In rural areas, the quality of medication use at telepharmacies is no worse than at traditional pharmacies. What are the implications for public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 11 publications
1
22
0
2
Order By: Relevance
“…The majority of the pharmacists agreed that telepharmacy could improve medication adherence and disease therapy management among patients. The results of our study were similar to the earlier study conducted by Hudd & Tataronis (2011) , and another study conducted by Pathak et al (2020) . These two studies did not find any difference in adherence rates between patients at a retail chain pharmacy and an urban telepharmacy-supported pharmacy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The majority of the pharmacists agreed that telepharmacy could improve medication adherence and disease therapy management among patients. The results of our study were similar to the earlier study conducted by Hudd & Tataronis (2011) , and another study conducted by Pathak et al (2020) . These two studies did not find any difference in adherence rates between patients at a retail chain pharmacy and an urban telepharmacy-supported pharmacy.…”
Section: Discussionsupporting
confidence: 92%
“…These two studies did not find any difference in adherence rates between patients at a retail chain pharmacy and an urban telepharmacy-supported pharmacy. This means that telepharmacy can provide a quality service similar to physical visits to the community pharmacies and improve patients’ quality of life ( Hudd & Tataronis, 2011 ; Pathak et al, 2020 ). These results are also supported by a study conducted by the United States Veterans Affairs (VA) integrated health care system, which used clinical pharmacist-led synchronous clinical video telehealth (CVT).…”
Section: Discussionmentioning
confidence: 99%
“…The BPA used Delphi's method to develop an innovative remote pharmaceutical care framework in response to the current needs of epidemic prevention and control. Different from the telepharmacy provided by a traditional pharmacy, clinic, or medical institution, such as support to clinical services, remote education and handling of "special pharmacies" on medication dispensing safety, and prescription and reconciliation of drug therapies (Baldoni et al, 2019;Le et al, 2020;Pathak et al, 2020;Zhou et al, 2020), this study describes and analyses the framework, the results, and effects of internetbased remote pharmacy services supported by multidisciplinary professional pharmacists with MTM certification quickly response to the COVID-19 epidemic, with social software on smartphones for patients' medication management and remote education. The innovative telepharmacy service aiming to provide a reference for international pharmacists.…”
Section: Introductionmentioning
confidence: 99%
“…This finding corroborates with previous similar studies that found that chronically ill patients take the most advantage of telepharmacy and home drug delivery. 37,38 What was of concern is that more than 60% of participants believed that home drug delivery might decrease pharmacist-patient contact time, thus compromising important drug information the patient should be aware of. Indeed, this is a true reality; previous studies revealed that the absence of patient counseling could significantly increase the risk for medication errors.…”
Section: Discussionmentioning
confidence: 99%